RELATIVE INCIDENCE OF GREATER MELON FLY,Dacus frontalis Becker AND CUCURBIT FLY, Dacus ciliates Loew ON CUCUMBER Cucumis sativus (L.) . - Redha S. AL-Jorany (Mesopotamia Journal of Agriculture)
Cucurbit fly, Dacus ciliates Loew is a major pest of cucurbitaceous vegetable fruits in many parts of Iraq. Infestation of another species , the Grater melon fruit fly, Dacus frontalis Becker was reported on Cucumber , Cucumis sativus (L.) as an economic insect in autaum cultivation in the middle of Iraq (Baghdad province) . Results showed that adults of D. frontalis Becker were more abundant than adults of D. ciliatus Loew . The percentage of these two pests was 92.79 and 7.21% on fruits with one infested location , and 96.97 , 3.03% from fruits with two infested location respectively . The number of adults emerged from fruits with one and two infested location was 7.09 and 6.34 , and 11.39 , 13.00 adults/ fruit for D. frontalis and D. ciliates respectively . The average total percent of fruit infestation was 62.57% during the period , October 1st to November 7th , 58.49% was due to infested by D. frontalis and 4.08 % to infestation by D. ciliatus. The number of larvae / fruit was 7.8 and 12.44 in fruits with one and two infested location respectively.